2015
DOI: 10.29173/lirg579
|View full text |Cite
|
Sign up to set email alerts
|

The usage of e-resources among agricultural researchers and extension staff in Tanzania

Abstract: This article investigates the accessibility and usage of e-resources among agricultural researchers and extension staff in five out of seven agricultural zones in Tanzania. The study identifies sources of e-resources used by these researchers and staff, as well as assessing their information literacy levels and the factors influencing their usage of e-resources. The research used a survey approach based on convenient non-probability sampling. Findings show that usage of e-resources from popular ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
3
16
0
Order By: Relevance
“…Individually, this result supported the findings of Lee, Hsiao and Purnomo (2014) that technology accessibility significantly influenced learners’ acceptance behaviour. In Tanzania, Mtega, Dulle, Malekani and Chailla (2014) found that availability of user names, password, accessibility, Internet access and bandwidth influenced agricultural researchers’ use of Research4Life databases. Rajan and Baral (2015) found that training positively influenced Enterprise Resource Planning system usage in India.…”
Section: Resultsmentioning
confidence: 99%
“…Individually, this result supported the findings of Lee, Hsiao and Purnomo (2014) that technology accessibility significantly influenced learners’ acceptance behaviour. In Tanzania, Mtega, Dulle, Malekani and Chailla (2014) found that availability of user names, password, accessibility, Internet access and bandwidth influenced agricultural researchers’ use of Research4Life databases. Rajan and Baral (2015) found that training positively influenced Enterprise Resource Planning system usage in India.…”
Section: Resultsmentioning
confidence: 99%
“…The is consistent with the findings of Gichamba, Wagacha and Ochieng (2017) which enumerated technical and detailed language on the platforms, lack of internet bundles to access the online platforms, poor or complete lack of internet access in some regions of the country, poor usability of the e-extension platform, illiteracy among some farmers, lack of electric power in remote areas making it difficult for the e-extension officer to frequently access information and poor mobile network coverage in some regions challenges to assessment of e-Extension platform of Kenya. A study by Mtega et. al.…”
Section: Information Exchanged Using Various E-resourcesmentioning
confidence: 99%
“…For users, E-resource has the advantages of time and place convenience, ability to search directly on text, ability to link to further reading material and ability to disseminate and share information (Quadri, 2012) According to Gichamba, Wagacha and Ochieng (2017), E-agricultural extension is an extension system that enables extension officers to reach out to farmers using a more efficient alternatives to a traditional system of agriculture using platforms like SMS, Interactive Voice Response (IVR), downloadable applications, Unstructured Supplementary Service Data (USSD) and mobile web and most services would be duplicated across different technologies in order to accommodate a larger clientele given the wide array of mobile devices among the target users. This helps to increase productivity, profitability and global competitiveness According to Mtega et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Forty-three Researchers and extension workers in the study possessed some measure of knowledge in search formulation, identifying appropriate information sources, selecting the right search tool and search evaluation based on their selfassessment which may not necessarily reflect their true skills. This could be attributed to the fact they may want to disguise ignorance, not realising how much more there is to learn (Mtega et al 2014). It is pertinent to emphasize based on the result presented in Table 7 that, training and retraining of respondents will help improve respondents' competence in the use of the internet.…”
Section: Rating Of Competence In Using the Internet To Access Online mentioning
confidence: 99%